Resveratrol Sensitizes Temozolomide-Resistant Glioblastoma Cells Through Mitogen-Activated Protein Kinase Pathway Inhibition and P-Glycoprotein Modulation - Rezaie, Maede; Nasehi, Mohammad; Shanehbandi, Dariush; Valizadeh, Amir; Yousefi, Bahman; Majidinia, Maryam (Drug Research, 2025)
Glioblastoma multiforme continues to pose a major therapeutic challenge due to its high level of treatment resistance and poor prognosis. Temozolomide is a standard chemotherapeutic agent, but resistance significantly limits its clinical efficacy. This study investigated the potential of resveratrol to overcome temozolomide resistance in glioblastoma cells by examining its effects on molecular mechanisms of drug resistance. Human glioblastoma cell lines U251 and temozolomide-resistant U251/temozolomide were utilized. Cellular viability was assessed using the MTT assay. Molecular mechanisms were evaluated through qRT-PCR, Western blotting, Rhodamine 123 accumulation, and apoptosis detection techniques. The study examined alterations in P-glycoprotein (P-gp) expression, mitogen-activated protein kinase/ERK signaling pathway, and apoptotic markers. Resveratrol significantly reduced the temozolomide resistance of U251/temozolomide cells, lowering the IC50 from 91.89 to 24.5 µM. Combined treatment demonstrated enhanced apoptotic cell death, significant downregulation of P-gp expression and activity, suppression of the mitogen-activated protein kinase/ERK signaling pathway, and upregulation of tumor suppressor miR-647. Resveratrol demonstrates potential as an adjuvant therapy by sensitizing temozolomide-resistant glioblastoma cells through multiple molecular mechanisms. It offers a promising approach to overcome chemotherapeutic resistance.
Keywords: Glioblastoma; Temozolomide resistance; MAPK/ERK inhibition; P-glycoprotein; miR-647